Elderly may benefit more from motor imagery training in gaining muscle strength than young adults: A systematic review and meta-analysis - Liu, Xiao J.; Ge, Sha; Cordova, Alberto; Yaghi, Zayd; Jiang, Bo Y.; Yue, Guang H.; Yao, Wan X. (Frontiers in Psychology, 2023)
Objective: The current review was aimed to determine the effectiveness of mental imagery training (MIT) on the enhancement of maximum voluntary muscle contraction (MVC) force for healthy young and old adults. Data Sources: Six electronic databases were searched from July 2021 to March 2022. Search terms included: ‘‘motor imagery training’’, ‘‘motor imagery practice’’, ‘‘mental practice’’, “mental training”, ‘‘movement imagery’’, “cognitive training”, ‘‘strength’’, ‘‘force’’, “muscle strength”, ‘‘performance’’, “enhancement”, ‘‘improvement’’, “development”, and ‘‘healthy adults’’ Study Selection and data extraction: Randomized controlled trials of MIT in enhancing muscle strength with healthy adults were selected. The decision on whether a study met the inclusion criteria of the review was made by two reviewers independently. Any disagreements between the two reviewers were first resolved by discussion between the two reviewers. If consensus could not be reached, then it would be arbitrated by a third reviewer. Data Synthesis: Twenty-five studies including both internal MIT and external MIT were included in meta-analysis for determining the efficacy of MIT on enhancing muscle strength and 22 internal MIT were used for subgroup analysis for examining dose-response relationship of MIT on MVC. Results: MIT demonstrated significant benefit on enhancing muscle strength when compared with no exercise, Effect Size (ES), 1.10, 95% confidence interval (CI), 0.89 – 1.30, favoring MIT, but was inferior to physical training (PT), ES, 0.38, 95% CI, 0.15 – 0.62, favoring PT. Subgroup analysis demonstrated that MIT was more effective for older adults (ES, 2.17, 95% CI, 1.57 – 2.76) than young adults (ES, 0.95, 95% CI, 0.74 – 1.17), p = .0002, and for small finger muscles (ES, 1.64, 95% CI, 1.06 – 2.22) than large upper extremity muscles (ES, 0.86, 95% CI, 0.56 – 1.16), p =.02. No significant difference was found in the comparison of small finger muscles and large lower extremity muscles, p =.19. Conclusions: MIT has better effects on enhancing MVC force compared to no exercise, but is inferior to PT. The subgroup analysis further suggests that older adults and small finger muscles may benefit more from MIT than young adults and large upper extremity muscles.